Evaluating the Migration Mortality Hypothesis Using Monarch Tagging Data - Taylor, Orley R.; Pleasants, John M.; Grundel, Ralph; Pecoraro, Samuel D.; Lovett, James P.; Ryan, Ann (Frontiers in Ecology and Evolution, 2020)
The decline in the eastern North American population of the monarch butterfly population since the late 1990s has been attributed to the loss of milkweed during the summer breeding season and the consequent reduction in the size of the summer population that migrates to central Mexico to overwinter (milkweed limitation hypothesis). However, in some studies the size of the summer population was not found to decline and was not correlated with the size of the overwintering population. The authors of these studies concluded that milkweed limitation could not explain the overwintering population decline. They hypothesized that increased mortality during fall migration was responsible (migration mortality hypothesis). We used data from the long-term monarch tagging program, managed by Monarch Watch, to examine three predictions of the migration mortality hypothesis: 1) that the summer population size is not correlated with the overwintering population size, 2) that migration success is the main determinant of overwintering population size and 3) that migration success has declined over the last two decades. As an index of the summer population size, we used the number of wild-caught migrating individuals tagged in the U.S. Midwest from 1998-2015. As an index of migration success we used the recovery rate of Midwest tagged individuals in Mexico. With regard to the three predictions: 1) the number of tagged individuals in the Midwest, explained 74% of the variation in the size of the overwintering population. Other measures of summer population size were also correlated with overwintering population size. Thus, there is no disconnection between late summer and winter population sizes. 2) Migration success was not significantly correlated with overwintering population size, and 3) migration success did not decrease during this period. Migration success was correlated with variation in NDVI, a measure of greenness of the southern part of the U.S. used by migrating butterflies for nectar. Thus, the main determinant of yearly variation in overwintering population size is summer population size with migration success being a minor determinant. Consequently, increasing milkweed habitat, which has the potential of increasing the summer monarch population, is the conservation measure that will have the greatest impact.